22q11.2 Deletion Syndrome is under-recognised in adult patients with tetralogy of Fallot and pulmonary atresia. Issue 8 (31st March 2010) - van Engelen, Klaartje; Topf, Ana; Keavney, Bernard D; Goodship, Judith A; van der Velde, Enno T; Baars, Marieke J H; Snijder, Simone; Moorman, Antoon F; Postma, Alex V; Mulder, Barbara J M
Abstract : Background: Three quarters of patients with 22q11.2 Deletion Syndrome (22q11.2DS) have congenital heart disease (CHD), typically conotruncal heart defects. Although it is currently common practice to test all children with typical CHD for 22q11.2DS, many adult patients have not been tested in the past and therefore 22q11.2DS might be under-recognised in adults. Objectives: To determine the prevalence of 22q11.2DS in adults with tetralogy of Fallot (TOF) and pulmonary atresia (PA)/ventricular septal defect (VSD) and to assess the level of recognition of the syndrome in adult patients. Methods: Patients were identified from CONCOR, a nationwide registry for adult patients with CHD. Inclusion criteria were diagnosis of TOF or PA/VSD and the availability of DNA. Patients with syndromes other than 22q11.2DS were excluded. Multiplex ligation-dependent probe amplification was used to detect 22q11.2 microdeletions. Results: 479 patients with TOF and 79 patients with PA/VSD (56% male, median age 34.7 years) were included and analysed. Twenty patients were already known to have 22q11.2DS. A 22q11.2 microdeletion was detected in a further 24 patients. Thirty-one patients with TOF (6.5%) had 22q11.2DS, whereas 13 patients with PA/VSD had 22q11.2DS (16.5%). Of all 22q11.2 microdeletions, 54% (24/44) were unknown before this study. Conclusion: This study shows that although the prevalence of 22q11.2DS in adults with TOF and PA/VSD is substantial, it is unrecognised in more than half of patients. As the syndrome has important clinical and reproductive implications, a diagnostic test should be considered in all adult patients with TOF and PA/VSD.